2016
DOI: 10.1007/s12291-016-0557-x
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Extraction and Solid Phase Extraction for Urinary Organic Acids: A Comparative Study from a Resource Constraint Setting

Abstract: Pre analytical process of extraction for accurate detection of organic acids is a crucial step in diagnosis of organic acidemias by GCMS analysis. This process is accomplished either by solid phase extraction (SPE) or by liquid-liquid extraction (LLE). Both extraction procedures are used in different metabolic laboratories all over the world. In this study we compared these two extraction procedures in respect of precision, accuracy, percent recovery of metabolites, number of metabolites isolated, time and cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Phosphoric acid and hydrochloric acid had similar performance in both liquid phases separation and in the chromatographic separation, although slightly higher peak areas were obtained using hydrochloric acid ( Figure S1 ). For that reason and according to the information found elsewhere, 22 hydrochloric acid was chosen for samples’ acidification. The influence of the acid was more prominent on the extraction of the acidic species (the SCFA), one of the most important groups of volatile metabolites in ruminant biological samples, since at low pH values (pH < 3) these compounds are in their unprotonated form, enabling its extraction from the sample to the organic phase.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphoric acid and hydrochloric acid had similar performance in both liquid phases separation and in the chromatographic separation, although slightly higher peak areas were obtained using hydrochloric acid ( Figure S1 ). For that reason and according to the information found elsewhere, 22 hydrochloric acid was chosen for samples’ acidification. The influence of the acid was more prominent on the extraction of the acidic species (the SCFA), one of the most important groups of volatile metabolites in ruminant biological samples, since at low pH values (pH < 3) these compounds are in their unprotonated form, enabling its extraction from the sample to the organic phase.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the LLE method was revealed to be as efficient as the other developed methods associated with GC-MS, namely, solid-phase extraction (SPE) and solid-phase microextraction (SPE), according to some recent studies in the literature (Table SII). Although these new methods have increased effectiveness in separation, the classic method by LLE remains the simplest and the less expensive one.…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al reported that solid phase extraction (SPE) provides a superior recovery to LLE [25]. However, LLE may be more cost effective than SPE [26] while still providing excellent recovery. Although we found an expected increase in MF with a decrease in concentration, the assay was still highly linear and met all standards of acceptable accuracy and precision (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%